TRANSLATION TECHNIQUES AND THEIR IMPACT ON THE READABILITY OF TRANSLATED BIBLE STORIES FOR CHILDREN - Nababan, Herianto; Nababan, Mangatur Rudolf; Santosa, Riyadi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2018)
Literatures for children are regarded as fictions. Research on translation of literatures for children ranging from comics and fairytales to short stories has much been done. Meanwhile, research on translation of bible stories for children, which are listed in the non-fictions and belong to sensitive texts has not so far been conducted. This research aims at investigating the impact of translation techniques on the readability of 43 translated bible stories for children. It employed the qualitative research method. Content analysis, focus group discussion, and questionnaire were used to collect its data. The data were qualitatively analyzed. The research findings show that the translator tended to use translation techniques oriented to target language (TL), indicating that the translator strives to domesticate the translations so ideologically that they are high readable. The dominance of established equivalent, explicitation, variation, transposition translation techniques is proof to the high readability of the translations. However, few of the data did not have a high readability due to the use of technical terms and new vocabulary. Thus, prior to publication of a translation work, it should be read by ideal target readers as to deal with the two factors and other inhibiting ones.Keywords: Translated bible stories for children, translation technique, translation method, translation ideology, readabilityTEKNIK PENERJEMAHAN DAN DAMPAKNYA TERHADAP KETERBACAAN TERJEMAHAN CERITA ALKITAB ANAKAbstrakKarya sastra anak digolongkan sebagai cerita fiksi Penelitian terjemahan karya sastra anak seperti komik, legenda, dan cerita pendek telah banyak dilakukan. Sementara itu, penelitian terjemahan cerita alkitab anak yang digolongkan dalam cerita non-fiksi dan teks sensitif sejauh ini belum pernah dilakukan. Tujuan penelitian ini adalah untuk mengetahui dampak teknik penerjemahan pada keterbacaan 43 cerita alkitab anak. Penelitian ini adalah penelitian kualitatif. Data dikumpulkan melalui analisis isi, fokus group discussion, dan kuesioner. Data dianalisis secara kualitatif. Temuan penelitian menunjukkan bahwa penerjemah cenderung menggunakan teknik penerjemahan yang dekat dengan bahasa sasaran, artinya penerjemah berusaha membuat terjemahan secara ideologi penerjemahan terdomestikasi dengan tujuan keterbacaannya tinggi. Dominasi teknik penerjemahan padanan lazim, eksplisitasi, variasi, dan transposisi merupakan bukti tingginya keterbacaan terjemahan itu. Namun demikian, ada beberapa data cerita tidak memiliki keterbacaan yang tinggi karena penggunaan istilah dan kosa kata baru. Oleh karena itu, sebelum karya terjemahan diedarkan, karya itu sebaiknya dibaca oleh pembaca target yang ideal dalam rangka mengatasi kedua faktor itu dan faktor penghambat lainnya.Kata Kunci: Cerita alkitab anak terjemahan, teknik penerjemahan, metode penerjemahan, ideologi penerjemahan, dan keterbcaan